Analisis Gaya Bahasa Repetisi dalam Mahallul Qiyam Maulid ad-Diba’i (Edisi Mil’u al- Awani) Perspektif Gorys Keraf - Fatimah, Salsabila Nova; Fakhrizal, Fakhrizal; Halim, Muhammad Fauzan; Raswan, Raswan; Dardiri, Dardiri (STAINI Press, 2025)
This study aims to analyze the use of repition as a linguistic style in the Mahallul Qiyam text, found un the book Mil’u al-Awani fi Tahqiq al Mawlid ad- Diba’I, which comprise 40 stanzas. The research focuses on identifying and classifying types of repetition based on a stylistic framework develop by Gorys Keraf. A descriptive-qualitative method is employed, with the primary data consisting of stanzas from Mahallul Qiyam, analyzed textually. The findings reveal that six out of the eight types of repetition identified by Gorys Keraf are present in the Mahallul Qiyam text: anaphora, epistrophe, mesodiplosis, tautotes, anadiplosis, and symploce. Among these, anaphora emerges as the most frequently used style. The repetition not only enhances the rhetorical strength of the text but also contributes to its aesthetic and spiritual resonance, which is characteristic of the Maulid recitation tradition. This research contributes to the field of stylistics, particularly in the analysis of religious texts, by examining the rhetorical and spiritual functions of repetition through the lens of Gorys Keraf’s theory